Evaluation of Recombinant Multi-Epitope Outer Membrane Protein-Based Klebsiella pneumoniae Subunit Vaccine in Mouse Model - Babu, Litty; Uppalapati, Siva R.; Sripathy, Murali H.; Reddy, Prakash N. (Frontiers in Microbiology, 2017)
Safety and protective efficacy of recombinant multi-epitopic subunit vaccine (r-AK36) comprising immunodominant antigens from outer membrane proteins (Omp’s) of Klebsiella pneumoniae namely OmpA and OmpK36 was evaluated in mouse model. r-AK36 was highly immunogenic and the hyperimmune sera reacted strongly with native OmpA and OmpK36 proteins from different K. pneumoniae strains. Hyperimmune sera showed cross reactivity with Omp’s of other Gram negative organisms. Humoral responses showed a Th2- type polarized immune response with IgG1 being the predominant antibody isotype. Anti-r-AK36 antibodies showed antimicrobial effect during in vitro MIC testing with values in range of 25-50 µg/ml on different K. pneumoniae strains. The recombinant antigen elicited three-fold higher proliferation of splenocytes from immunized mice indicating possible T-cell clonal proliferation and differentiation into effector cells. Anti-r-AK36 antibodies also exhibited in vitro biofilm inhibition property. Subunit vaccine r-AK36 immunization promoted induction of anti-inflammatory cytokines in immunized mice. When r-AK36 immunized mice were challenged with 3xLD100 dose, ~80 % of mice survived beyond the observation period. Passive antibody administration to naive mice protected them (67 %) against the lethal challenge. Since the targeted OMPs are conserved among all K. pneumoniae serovars and due to the strong nature of immune responses, r-AK36 subunit vaccine could be a safe and cost effective candidate against klebsiellosis.